Portuguese coaches` perceptions of and preferences for knowledge sources related to their professional background - Mesquita, I.; Isidro, S.; Rosado, A. (Journal of Sports Science & Medicine, 2010)
The purpose of this study was to analyse Portuguese coaches' perceptions of, and preferences for, knowledge sources as related to professional background; namely academic education level, coach education level and coaching experience. The study's participants comprised 336 Portuguese coaches from twenty-two sports. A questionnaire was used to identify coaches' demographic characteristics and representations about their preferred sources of coaching knowledge. MANOVA using Tukey's HSD test was used to compare groups. The results highlighted that coaches perceived that coaching knowledge is built from a broad range of sources from personal coaching and playing experiences to more explicit formal, informal and non-formal learning situations. Results indicated that the coaches ascribed more importance to experiential sources such as working with experts, learning by doing, interacting with peer coaches and attending informal seminars and clinics, than to the formal learning situations provided by the national coaching certification programs. Differences, however, were found in that coaches who had a greater background within higher education (physical) and sport valued informal and non-formal learning sources more than did coaches who were defined as not coming from an academic background. The findings point to the importance of developing new learning, experientially-based, opportunities within the Portuguese context, where curricula content continues to be delivered via didactic means.